Lobophorin K, a New Natural Product with Cytotoxic Activity Produced by Streptomyces sp. M-207 Associated with the Deep-Sea Coral Lophelia pertusa - Alfredo Braña; Aida Sarmiento-Vizcaíno; Miguel Osset; Ignacio Pérez-Victoria; Jesús Martín; Nuria De Pedro; Mercedes De la Cruz; Caridad Díaz; Francisca Vicente; Fernando Reyes; Luis García; Gloria Blanco (Marine Drugs, 2017)
The present article describes the isolation of a new natural product of the lobophorin family, designated as lobophorin K (1), from cultures of the marine actinobacteria Streptomyces sp. M-207, previously isolated from the cold-water coral Lophelia pertusa collected at 1800 m depth during an expedition to the submarine Avilés Canyon. Its structure was determined using a combination of spectroscopic techniques, mainly ESI-TOF MS and 1D and 2D NMR. This new natural product displayed cytotoxic activity against two human tumor cell lines, such as pancreatic carcinoma (MiaPaca-2) and breast adenocarcinoma (MCF-7). Lobophorin K also displayed moderate and selective antibiotic activity against pathogenic Gram-positive bacteria such as Staphylococcus aureus.